Cellular remodeling of ovarian follicular epithelial cells transmits an obligate nutritional endosymbiont in a scale insect - Ojaswini; Sourajyoti Pal; Aranya Dhibar; Kailash Chandra; Annapoorni Rangarajan; Shantanu P. Shukla (Proceedings of the National Academy of Sciences, 2026)
Many insects show complex associations with vertically transmitted endosymbionts. Here, we describe unique cellular remodeling of the oocyte’s follicular epithelial cells into endosymbiont-bearing tubular structures in the ensign scale insect Insignorthezia insignis (Hemiptera: Ortheziidae). Vitellogenic oocytes develop a bulge-like distension at the posterior pole. Here, follicular epithelial cells undergo extensive cellular reorganization, remodeling their actin cytoskeleton and plasma membrane to produce cellular protrusions. These tubular protrusions, which are densely packed with the endosymbiont, subsequently detach from the epithelial layer and migrate along the developing embryonic germ band, thus facilitating the endosymbiont’s transovarial transmission. We further report a flavobacterial endosymbiont with an eroded genome of 0.86 Mb that encodes genes for amino acids, vitamins, and fatty acid biosynthesis. Genes for pantothenate and biotin biosynthesis, which were absent from the endosymbiont genome, were found to be horizontally acquired by the host genome from bacteria other than the symbiont, demonstrating host-symbiont metabolic complementarity and genome coevolution. The symbiont’s nutrient-provisioning genes were expressed both in the host’s adult stage, which feeds exclusively on nutrient-deficient plant phloem, as well as in the embryonic stages. Notably, experimental depletion of the endosymbiont from the embryonic stage caused high mortality, while the surviving nymphs exhibited severe phenotypic abnormalities, including the absence of body wax. Our results highlight the intricate and synergetic coordination between endosymbionts and the developing embryo, indicating broader phenotypic consequences in scale insects via symbiont-mediated nutritional supplementation.